Performance of a supercritical CO2 bottoming cycle for aero applications - Jacob, Florian; Rolt, Andrew Martin; Sebastiampillai, Joshua Marius; Sethi, Vishal; Belmonte, Mathieu; Cobas, Pedro (MDPI, 2017)
By 2050, the evolutionary approach to aero engine research may no longer provide meaningful returns on investment, whereas more radical approaches to improving thermal efficiency and reducing emissions might still prove cost effective. One such radical concept is the addition of a secondary power cycle that utilizes the otherwise largely wasted residual heat in the core engine’s exhaust gases. This could provide additional shaft power. Supercritical carbon dioxide closed-circuit power cycles are currently being investigated primarily for stationary power applications, but their high power density and efficiency, even for modest peak cycle temperatures, makes them credible bottoming cycle options for aero engine applications. Through individual geometric design and performance studies for each of the bottoming cycle’s major components, it was determined that a simple combined cycle aero engine could offer a 1.9% mission fuel burn benefit over a state-of-the-art geared turbofan for the year 2050. However, the even greater potential of more complex systems demands further investigation. For example, adding inter-turbine reheat (ITR) to the combined cycle is predicted to significantly improve the fuel burn benefit.
Keywords: supercritical carbon dioxide; supercritical carbon dioxide; recuperated bottoming cycle; geared turbofan; Span & Wagner; Equation of State; Printed Circuit Heat Exchanger; ULTIMATE; Flightpath 2050